STRUCTURAL CHANGE AND MODELS OF STRUCTURAL ANALYSIS: THEORIES, PRINCIPLES AND METHODS - SCHILIRÒ, Daniele (Journal of Advanced Research in Law and Economics; Vol 3 No 2 (2012): JARLE Volume III, Issue 2(6), Winter 2012, 2017)
Structural change indicates essentially a qualitative transformation and evolution of the economic systems, usually marked by technological progress and organizational changes. Technological factors, knowledge, institutions are all elements that contribute to the process of structural change.  Schumpeter (1912, 1939) has certainly been one of the most influential economists who has analysed and explained the process of development and at the same time took into consideration the mechanisms of transformation of the production system. This contribution focuses on the models of structural analysis, particularly on the methods and principles that such models adopt; in this context, structural change becomes the underlying dominant theme of the present work. The investigation of the models of structural analysis and of theories of structural changes carried out in this contribution has a double meaning. On the one hand, it allows picking up several essential principles that characterize these models; on the other hand, it should allow us to examine some important methodological issues, such as different methods of decomposition of the productive systems, the problem of complexity and the strategies to reduce complexity.